1980
DOI: 10.1056/nejm198011203032104
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Phenylketonuria and Hyperphenylalaninemia

Abstract: Since many women with phenylketonuria (PKU) will have children of their own, we were interested in ascertaining the effect of maternal PKU and hyperphenylalaninemia on the offspring of such women. We reviewed the literature on this subject and obtained additional unpublished data through an international survey. Data were collected on 524 pregnancies in 155 women; in 34 pregnancies a low-phenylalanine diet was begun after or shortly before pregnancy was established. Among untreated pregnancies, the frequencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

1982
1982
1999
1999

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 525 publications
(62 citation statements)
references
References 21 publications
4
54
0
Order By: Relevance
“…Although the influence of the BALB/c maternal environment may in turn reflect autosomal genetic factors possessed by the mother, as has been shown for certain Mendelian gene mutations 10,16 , the maternal environment effect on offspring development is not the same kind of genetic influence on the growing mouse as is the mouse's own set of genes inherited via egg and sperm. From the perspective of the growing mouse it is strictly an environmental influence, although some human theorists might prefer to see it as an indirect genetic influence.…”
Section: Discussionmentioning
confidence: 99%
“…Although the influence of the BALB/c maternal environment may in turn reflect autosomal genetic factors possessed by the mother, as has been shown for certain Mendelian gene mutations 10,16 , the maternal environment effect on offspring development is not the same kind of genetic influence on the growing mouse as is the mouse's own set of genes inherited via egg and sperm. From the perspective of the growing mouse it is strictly an environmental influence, although some human theorists might prefer to see it as an indirect genetic influence.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that persistent maternal hyperphenylalaninemia during pregnancy is harmful to the fetus, leading to increased risk of cardiac anomalies, intrauterine growth retardation, microcephaly, and mental retarda tion. Dietary therapy instituted after pregnancy was detected was not effective in preventing these cogenital defects (114). It has been suggested that restrict ing the diet both prior to and during pregnancy may be effective.…”
Section: Analysis Of Maternal Effe Ctsmentioning
confidence: 99%
“…In principle, it should prove possible to reduce risk by putting women with this disorder on a phenylalanine low diet before they attempt to become pregnant. If the diet is introduced after pregnancy occurs, it brings little benefit because of damage done during the first six weeks of fetal development (Lenke & Levy 1980). Preventing environmental hazards to the brain Accidents and poisonings are the leading causes of childhood and adolescent mortality and morbidity in the United States.…”
Section: Neonatal Screeningmentioning
confidence: 99%